Robust optimal placement of dampers in structures with set-back and eccentricity using sensitivity analysis for integrated transfer function. (2016) - Kawamoto, Taito; Fujita, Kohei; Tsuji, Masaaki; Takewaki, Izuru
An efficient and systematic procedure is proposed for finding an optimal damper placement to minimise an integrated dynamic compliance of a three-dimensional shear set-back building with eccentricity. The integrated dynamic compliance is expressed in terms of an area of a transfer function with respect to frequency. The integrated dynamic compliance is minimised subject to a constraint on the sum of the damping coefficients of added dampers. A sensitivity-based optimisation algorithm is developed and the optimal damper placement is determined. Different types of integrated transfer function are used as the objective function in the algorithm. The proposed algorithm enables one to find an optimal damper placement sequentially with respect to gradually increasing damper capacity level. The main outcomes of this study are summarised as follows. First, the optimisation algorithm proposed in this paper is less affected by characteristics of input ground motions than other optimisation algorithms based on minimisation of transfer function amplitude or maximisation of the lowest-mode damping ratio. Secondly, the optimisation algorithm is applicable to realistic and complex structural models affected by both translational and torsional modes.